Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/ijo.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief perturbations in energy balance on indices of glucose homeostasis in healthy lean men

Abstract: BACKGROUND:Little is known about the effects of short-term caloric restriction (CR) and overfeeding (OF) on glucose homeostasis in healthy lean individuals. In addition, it remains unclear whether the effects of CR and OF are reversed by a complementary feeding period. METHODS: Ten healthy men participated in two cycles of controlled 7-day periods of CR and refeeding (RF; protocol A), and OF and CR (protocol B) at ±60% energy requirement. At baseline, insulin sensitivity (IS) was assessed by euglycemic clamp (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 51 publications
5
43
2
Order By: Relevance
“…During the preintervention periods and at the end of refeeding, IS was assessed by the hyperinsulinemiceuglycemic clamp technique according to deFronzo et al (40) as previously described (32,41). Whole-body IS was determined during the last 20 min of the hyperinsulinemic glucose clamp as steady-state glucose disposal rate calculated from the mean rate of exogenous glucose infusion corrected for glucose space [M-value, mg/(kg 3 min)].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the preintervention periods and at the end of refeeding, IS was assessed by the hyperinsulinemiceuglycemic clamp technique according to deFronzo et al (40) as previously described (32,41). Whole-body IS was determined during the last 20 min of the hyperinsulinemic glucose clamp as steady-state glucose disposal rate calculated from the mean rate of exogenous glucose infusion corrected for glucose space [M-value, mg/(kg 3 min)].…”
Section: Methodsmentioning
confidence: 99%
“…Fat mass and fat-free mass were assessed by airdisplacement plethysmography (BOD POD, Cosmed) as described in detail elsewhere (37). Liver fat was determined by MRI (Magnetom Avanto 1.5-T Siemens) along with the 2-point Dixon method with a volume interpolated breathhold examination as previously described (32). Briefly, a T1-weighted gradient-echo sequence with in-phase and out-of-phase imaging was performed using the following variables: repetition time, 10.4 ms; echo time, 4.76 (in-phase) and 7.14 (opposedphase) ms; flip angle, 10°; matrix, 80 3 128; and field of view, 440 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, consistent with our hypothesis, we show that an increase in lipid metabolites are associated with defects in tissue insulin action, suggesting that lipotoxicity is a generalised mechanism associated with the induction of insulin resistance in individual tissues of mice. Studies in rodents [7,[19][20][21]23], dogs [24] and humans [25][26][27], have shown that short-term exposure to HFD/overfeeding (3-28 days) results in the rapid development of insulin resistance and glucose intolerance. Often these changes occur with only modest increases in fat mass, highlighting that metabolic defects occur prior to the onset of obesity and do not require extensive periods of fat feeding.…”
Section: Discussionmentioning
confidence: 99%